(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2023)
Chromatography-mass spectrometry data is analyzed in two ways. According to the first method, the mass spectra recorded at various points of the mass chromatogram are analyzed by comparison with the mass spectra of the standards collected in the database